Continuous Versus Intermittent Infusion of Furosemide in Acute Decompensated Heart Failure - Thomson, Margaret R.; Nappi, Jean M.; Dunn, Steven P.; Hollis, Ian B.; Rodgers, Jo E.; Van Bakel, Adrian B. (Journal of cardiac failure, 2010)
Despite advances in the treatment of chronic ambulatory heart failure, hospitalization rates for acute decompensated heart failure (ADHF) remain high. Although loop diuretics are used in nearly all patients with ADHF to relieve congestive symptoms, optimal dosing strategies remain poorly defined. This was a prospective, randomized, parallel-group study comparing the effectiveness of continuous intravenous (cIV) with intermittent intravenous (iIV) infusion of furosemide in 56 patients with ADHF. The dose and duration of furosemide as well as concomitant medications to treat ADHF were determined by physician preference. The primary end point of the study was net urine output (nUOP)/24hours. Safety measures including electrolyte loss and hemodynamic instability were also assessed. Twenty-six patients received cIV and 30 patients received iIV dosing. The mean nUOP/24hours was 2098±1132mL in patients receiving cIV versus 1575±1100mL in the iIV group (P=.086). The cIV group had significantly greater total urine output (tUOP) with 3726±1121mL/24hours versus 2955±1267mL/24hours in the iIV group (P=.019) and tUOP/mg furosemide with 38.0±31.0mL/mg versus 22.2±12.5mL/mg (P=.021). Mean weight loss was not significantly different between the groups. The cIV group experienced a shorter length of hospital stay (6.9±3.7 versus 10.9±8.3 days, P=.006). There were no differences in safety measures between the groups. The cIV of furosemide was well tolerated and significantly more effective than iIV for tUOP. In addition, continuous infusion appears to provide more efficient diuresis.